A rare cause of severe periorbital edema and dermonecrotic ulcer of the eyelid in a child: brown recluse spider bite - Taşkesen, Mustafa; Akdeniz, Sedat; Taş, Taşkin; Keklikçi, Uğur; Taş, Mehmet Ali (The Turkish Journal of Pediatrics, 2011)
Spider bites are a worldwide problem. Brown recluse spider bites can lead to severe local or systemic clinical effects, such as edema, necrotic ulcer, rashes, fever, chills, nausea, vomiting, malaise, arthralgia, myalgia, hemolysis, leukocytosis, disseminated intravascular coagulation, renal failure, and death. Eyelid bites from brown recluse spiders are rare. We report a child with severe facial edema and a dermonecrotic ulcer on the eyelid. Upon laboratory examination, leukocytosis with a significant left shift was detected. The patient was treated with antibiotics, systemic corticosteroid and conservative therapy that included saline compresses and ocular lubrication. No surgical excision was required. Vision was not impaired. A dermonecrotic ulcer is a severe complication of brown recluse spider bites. Since the diagnosis is difficult, clinical and epidemiological findings and a detailed history are important for an accurate diagnosis.